Pendampingan Penulisan Artikel Ilmiah Berbasis AI untuk Mendorong Budaya Riset Di Kalangan Pendidik - Kuswanto ,; Sofia Tri Septiawati; Sutarum ,; Dita Pratama (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of artificial intelligence (AI) technology has opened new opportunities to support the scientific writing process, especially among educators. However, the level of AI utilization by teachers still faces challenges in aspects of digital literacy, academic ethics, and the sustainability of research practices. This community service activity aims to enhance digital literacy competence and AI-based scientific article writing skills for educators at SMK PGRI Sukodadi and SMK PGRI 1 Lamongan. The method used is participatory action through online training and mentoring via the Zoom platform, involving 52 educators. The activity was carried out in four stages: AI literacy training, article writing practice, synchronous mentoring, and evaluation of training outcomes and the formation of a writers' community. The results of the activity showed a significant improvement in digital literacy, academic self-confidence, and the quality of participants' writing structure. Participants demonstrated a better understanding of the use of AI as an ethical and productive writing aid. In addition, internal collaborative initiatives were established within the school, such as manuscript discussion forums and joint publication plans, marking the emergence of a mini research culture in the school environment. Although there were technical challenges such as limited internet connectivity and practice time, systematic mentoring proved effective in overcoming these obstacles. These findings underscore the importance of structured and sustainable strategies to strengthen educators' digital literacy so that AI technology becomes not only a technical tool but also an instrument to drive a research culture. Such mentoring has the potential to serve as a model for developing educators' competencies in Indonesia's vocational education ecosystem, while also supporting the improvement of the quality of educators' scientific publications.